1994
DOI: 10.1093/geronj/49.4.s176
|View full text |Cite
|
Sign up to set email alerts
|

Women's Work and Caregiving Roles: A Life Course Approach

Abstract: This study drew on a life course approach and a sample of 293 women from four birth cohorts in upstate New York to examine the relationship over time between women's paid work and their informal caregiving of aging or infirm relatives. We find that such caregiving is an increasingly likely role for women, both as they age and across birth cohorts. One in four (24%) women became caregivers at some time between ages 35-44, and over one in three (36%) of these same women became caregivers between ages 55-64. Only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(135 citation statements)
references
References 0 publications
6
126
0
3
Order By: Relevance
“…Variables on the carer's or care recipient's income or on their human capital investment are also often incomplete or missing although they are important determinants of labor supply (Johnson and Lo Sasso, 2000). Another problem is the small number of observations in some of the data sets (Pezzin and Schone, 1999;Stone and Short, 1990;Moen et al, 1994 The analysis uses panel data and, therefore, checks for unobserved heterogeneity which is likely to be substantial in caregiving decisions. In addition, the endogenous relation between employment and care is taken into account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Variables on the carer's or care recipient's income or on their human capital investment are also often incomplete or missing although they are important determinants of labor supply (Johnson and Lo Sasso, 2000). Another problem is the small number of observations in some of the data sets (Pezzin and Schone, 1999;Stone and Short, 1990;Moen et al, 1994 The analysis uses panel data and, therefore, checks for unobserved heterogeneity which is likely to be substantial in caregiving decisions. In addition, the endogenous relation between employment and care is taken into account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prevalence of midlife caregiving responsibility for elders is only expected to increase, too, as we become ever more an "aging" and "aged" society (Coward, Horne, & Dwyer, 1992). Demographic trends that have resulted in longer lives, smaller families, higher rates of divorce, lower rates of marriage and remarriage, and higher rates of women's employment than previously mean that we can expect caregiving for frail elders will fall on relatively fewer shoulders in the years ahead, and that the risk of becoming a caregiver at some time or multiple times over the life course is likely to increase (Coward et al, 1992;Marks, 1996;Moen, Robison, & Fields, 1994).…”
Section: Does It Hurt To Care? Caregiving Work and Family Conflict mentioning
confidence: 99%
“…This theoretical orientation suggests that caregiving be viewed as a life course role that one is likely to enter and exit one or more times during adulthood (Moen, Robison, & Fields, 1994). Following life course perspective principles (Elder, 1992), in order to understand the likely well-being consequences of the caregiving role, it becomes useful to consider the developmental timing of transitions into and out of the caregiver role, the intersection of other roles in relation to the caregiving role, the changing historical context for enactment of the caregiving role, and the cumulative patterns of caregiving across the life courses of varying birth cohorts (Moen, Robison, & Fields, 1994).…”
Section: A Life Course Role-identity Approach To Caregivingmentioning
confidence: 99%
“…In an earlier study by Moen, Robison, and Fields (1994), care giving was found to be positively associated with mastery in female caregivers in their 50's and early 60's. In many cases, caregiving duties are perfonned in conjunction with full or part.. time work (Ruhm, 1996).…”
Section: Well-being and Caregivingmentioning
confidence: 74%